A Study on Evaporative Resistances of Two Skins Designed for Thermal Manikin Tore under Different Environmental Conditions (Journal of Fiber Bioengineering and Informatics, 2018)
A cotton skin and a waterproof but permeable Gore-Tex skin were designed for the thermalmanikin &#8220Tore&#8221 to simulate different sweating styles (the wet cotton skin inside and Gore-Texskin outside to simulate the sweating style of thermal manikin &#8220Walter&#8221, and Gore-Tex skin insidewith wet cotton skin outside to simulate the sweating style of thermal manikins &#8220Newton&#8221). Theevaporative resistances of two skin combinations with clothing ensembles were compared at differentenvironmental conditions. In addition, the total evaporative resistance of clothing ensemble wascalculated by both the heat loss method (option 1) and the mass loss method (option 2) according toASTM F 2370. We found that the effect of different sweating mechanisms on the clothing evaporativeresistance should be considered. The results showed that the total evaporative resistances calculatedby option 2 were more accurate than values in option 1 under the isothermal condition. It was alsofound that differences of the total evaporative resistance between two skin combinations with clothingensembles decreased with the increasing clothing ensemble layer. In a non-isothermal condition, thetotal evaporative resistance calculated by option 1 was more accurate than the value obtained in option2, which was due to the lower ambient temperature and condensations between each adjacent layer.
Keywords: evaporative resistance; heat loss; fabric skin; sweating simulation; thermal manikin; isothermal